Possible relationship between the resistin gene C-420G polymorphism and colorectal cancer in a Turkish population - Düzköylü, Yiğit; Arıkan, Soykan; Turan, Saime; Yaylım, İlhan and Doğan, Mehmet Baki and Sarı, Serkan and Ersöz, Feyzullah and Zeybek, Ümit and Tımırcı Kahraman, Özlem and Çelikel, Burcu and et al. (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: In recent years, with improvements in genotyping, a possible relationship between obesity-related gene polymorphisms and colorectal cancer (CRC) has been studied. The promoter region C-420G of the resistin gene is believed to have an important role in the development of malignancy. We prospectively evaluated the possible effect of the resistin C-420G polymorphism on the risk and prognosis of CRC. Materials and Methods: One hundred twenty-three patients with CRC and 79 healthy individuals were included in the study. Blood samples were genotyped, and the relationship between the resistin C-420G polymorphism and demographic characteristics and tumor features was evaluated. Results: No statistically significant difference was found in genotype distribution between the patient and control groups and among patients in the means of gender, biochemical findings, and tumor characteristics (p>0.05). Conclusion: The relationship between the C-420G polymorphism and various diseases has been evaluated in many studies to date. With the increased importance of obesity in etiopathogenesis, studies have focused on CRC. According to our results, the GG genotype may be associated with a decreased CRC risk. Our study is important because to our knowledge, it is the first one to be conducted in a Turkish population to date, but we believe that more patients and controls are needed to obtain statistically significant results.